A systematic review: Botany, phytochemistry, traditional uses, pharmacology, toxicology, quality control and pharmacokinetics of Ilex rotunda Thunb. (15th November 2022) - Zeng, Wei; Cui, Hui; Yang, Weiqun; Zhao, Zhongxiang
Abstract: Ethnopharmacological relevance: Ilex rotunda Thunb. ( I. rotunda ) is an Ilex species of Aquifoliaceae, widely distributed in East Asia. Its dried bark is commonly used as a medicinal part in the field of traditional Chinese medicine (TCM), named Ilicis Rotundae Cortex. This medicinal plant is commonly used for clearing heat and removing toxin, draining dampness and relieving pain in TCM to treat tonsillitis, acute gastroenteritis, gastric and duodenal ulcer, rheumatism, traumatic injury, and so on. It also has significant development value on lipid-lowering, hepatoprotection and anti-inflammation, but the potential mechanism needs to be further explored. Aim of the review: More and more medicinal substances are being discovered in I. rotunda with multiple biological activities, which help to advance the ethno-pharmacological research in I. rotunda . However, to date there is a lack of a systematic summary of research progress on I. rotunda . This review aims to provide a critical summary of the current studies on I. rotunda . The progress in research on botany, phytochemistry, traditional uses, pharmacology, toxicology, quality control and pharmacokinetics of the plant is discussed. It hopes to provide useful references and guidance for the future directions of research on I. rotunda . Materials and methods: Studies of I. rotunda were collected via Google Scholar and Baidu Scholar, PubMed, ScienceDirect, SciFinder, Web of Science, China National Knowledge Infrastructure (CNKI), WANFANG DATA and libraries. Some local books, official websites, PhD or MS's dissertations were also included. The literature cited in this review covered the period from 1956 to January 2022. Results: Analysis of the literature indicates that I. rotunda is a potentially valuable herbal medicine for the therapeutic of various diseases. To date, 120 compounds were found and identified in I. rotunda, mainly including triterpenoids, phenylpropanoids, etc. Modern pharmacological studies also found that the plant has the activities of protecting the cardiovascular system, lowering lipids and protecting the liver, as well as being an anti-inflammatory, anti-tumor and antibacterial. Conclusions: This review summarizes the results from current studies of I. rotunda . However, the current explanation seems insufficient and unsatisfactory, in terms of the relationships between the traditional uses and the modern pharmacological activities, the mechanisms and the material basis. Thus, a critical and comprehensive evaluation is necessary to explore its future research prospects and development direction. Graphical abstract: Image 1 Highlights: The highlights of the paper are: Anti-inflammatory and TCM efficacy are linked in Ilicis Rotundae Cortex (IRC). Anti-lipid metabolism disorders and TCM efficacy are linked in IRC. Rotundic acid, pedunculoside and syringin could be key medicinal substances. This is the first systematic critical review of studies on Ilex rotunda Thunb.